PERLINDUNGAN HUKUM BAGI PEREMPUAN KORBAN KEKERASAN DALAM RUMAH TANGGA - Brahmandya, I Gusti Ngurah Agung; Wirasila, A. A. Ngr.; Parwata, I Gusti Ngurah (Kertha Wicara : Journal Ilmu Hukum; Vol. 01, No. 03, Juli 2013)
Prevention and control of violence in society is increasing. Including violence against women has historically been known, but the incident has not been placed as Legal Social Problem. If there is violence in the domestic sphere is always resolved with penal Code of Criminal Law. Examined from the perspective of the normative with the enactment of Law No. 23 Year 2004 on the elimination of violence in the home is an umbrella law for victims of domestic violence. There are several arguments why women as victims of domestic violence need legal protection (protection of human rights or) compensation (restitution, compensation, security / social welfare benefits).
Keywords: Penal, Domestic violence, compensation